(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
This paper explores the concept of anthropomorphism in antiquity and its significant influence on contemporary films and special effects. Anthropomorphism, the attribution of human traits to non-human entities, was central to ancient Greek religion and theatre, shaping the portrayal of gods and other supernatural beings. This work analyzes these early anthropomorphic representations and their impact on modern special effects, providing a historical overview of special effects in film and establishing a connection between ancient theatrical practices and contemporary cinematic techniques. The qualitative critical discussion analysis method was adopted to study the explored concepts. The study demonstrates that contemporary films and special effects owe much to the anthropomorphic spectacles of antiquity, which paved the way for the visual wonders we see in today’s films.